Collision tumor of the kidney composed of clear cell carcinoma and collecting duct carcinoma treated with cabozantinib and nivolumab - Salazar Mejía, Carlos Eduardo; Oyervides Juárez, Víctor Manuel; Wimer Castillo, Blanca Otilia; Vidal Gutiérrez, Oscar; Garza Guajardo, Raquel; Grande, Enrique (Elsevier, 2020)
Collision tumors (CT) refer to the phenomenon where two or more apparently different and unrelated tumors occur within the same location in an organ, forming the same lesion. We present the first case of renal CT with a mixed component of clear cell carcinoma and collecting duct carcinoma (CDC) with rhabdoid and sarcomatoid characteristics treated with the combination of cabozantinib and nivolumab. A 47-year-old man arrived at our clinic referring persistent dry cough, accompanied by a weight loss of 12 kg in the previous two months. Imaging studies revealed bilateral pulmonary lesions of metastatic appearance associated with a large tumor in the left kidney. After radical nephrectomy the histopathological report revealed a renal cell carcinoma (collecting duct carcinoma 85% and clear cell carcinoma 15%). The patient was included in a treatment protocol based on cabozantinib 40 mg QD plus nivolumab 240 mg every 15 days, obtaining a partial response after two months. This response was maintained for 12 months after initiation of systemic treatment. This is the first documented case of renal CT with a CDC component that obtained a partial response to combined treatment with immunotherapy and target therapy as first-line treatment; obtaining the longest overall survival reported in the setting of a metastatic renal CT with this histological combination. We need to expand the knowledge regarding the treatment of metastatic CDC, either as a single entity or as a component of a renal CT, in order to offer the best possible therapeutic outcome.